"It's not just about football all the time either": transnational athletes' stories about the choice to migrate. Issue 1 (2nd January 2021) - Ely, George; Ronkainen, Noora J.
Abstract : Due to the growing mobility of athletes and coaches, cultural transitions have recently emerged as a distinct area of interest within athletic career development literature. The purpose of the present study was to extend understanding of cultural transitions by investigating the experiences of transnational athlete migrants within European American Football. Nine male athletes who had crossed national borders to play at least one full season of American Football in Europe were interviewed twice with a focus on discerning narrative meaning-making associated with the choice to migrate and the consequences of these narratives for cultural adaptation and engagement with the host site. Through thematic narrative analysis, we identified three narrative types, " a step across the pond: fleeing America", " a step up: proving myself", and " vehicle for travel: it's a paid vacation", each representing different life themes that had implications for adaptation and well-being. The findings challenge dominant discourses regarding the reasons why athletes migrate while tracing different ways in which adaptation and belonging can be achieved.